2016
DOI: 10.1021/acs.inorgchem.6b01369
|View full text |Cite
|
Sign up to set email alerts
|

Hydride-Based Electride Material, LnH2 (Ln = La, Ce, or Y)

Abstract: In view of the strong electron-donating nature of H(-) and extensive vacancy formation in metals by hydrogen insertion, a series of LnH2+x (Ln = La, Ce, or Y) compounds with fluorite-type structures were verified to be the first hydride-based electride, where itinerant electrons populating the cage are surrounded by H(-) anions. The electron transfer into the cage probably originates from Ln-cage covalent interaction. To the best of our knowledge, anion-rich electrides are extremely rare, and a key requirement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
83
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 39 publications
3
83
0
Order By: Relevance
“…It is interesting to compare Mg 2 Si with arecently reported fluorite-type electride,L aH 2 (Figure 1b). [7] LaH 2 is au nique material in which the anionic electron is surrounded by eight H À anions.A ss hown in the Supporting Information, Figure S3, we can see strong La d y 2 overlap (mirroring the Si d contributions in Mg 2 Si)a cross the void site at the Xp oint (measured by the V sp DOS), which creates af unction isolobal to the CBM state in Mg 2 Si. In this way,t he cavity site plays an important role in the electronic structure of both compounds as bonding states arise from covalent interactions along short cation-cation contacts around the cages.A sw e will discuss further below,t his view offers clues to the development of functional materials utilizing cavity spaces.…”
mentioning
confidence: 90%
See 3 more Smart Citations
“…It is interesting to compare Mg 2 Si with arecently reported fluorite-type electride,L aH 2 (Figure 1b). [7] LaH 2 is au nique material in which the anionic electron is surrounded by eight H À anions.A ss hown in the Supporting Information, Figure S3, we can see strong La d y 2 overlap (mirroring the Si d contributions in Mg 2 Si)a cross the void site at the Xp oint (measured by the V sp DOS), which creates af unction isolobal to the CBM state in Mg 2 Si. In this way,t he cavity site plays an important role in the electronic structure of both compounds as bonding states arise from covalent interactions along short cation-cation contacts around the cages.A sw e will discuss further below,t his view offers clues to the development of functional materials utilizing cavity spaces.…”
mentioning
confidence: 90%
“…Our ongoing theoretical exploration of semiconductors containing electronically active cavity spaces has revealed that the antifluorite type compound Mg 2 Si (Figure 1a), ak nown material for thermoelectric applications, [5] is au nique semiconductor whose conduction band minimum corresponds to states associated with void spaces. [7] . Crystal structures of a) Mg 2 Si and Na 2 S(antifluorite structure) [6] and b) the anion-rich LaH 2 electride (fluorite structure).A n electron density isosurface map plotted at 5m À3 for states near the E F is superimposed on the structure of LaH 2 .This electron density is concentrated on the central cavity site (V).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[9][10][11][12][13][14] To date, fifteen(seven inorganic and eight organic)s olide lectrides have been reported, eight of which are stable at room temperature. [13,[15][16][17][18][19] In some other cases,t he electride character is revealed only at high pressure. [20][21][22][23][24][25][26][27] Molecular electrides [28] are another type of electrides that have an electron( or as ignificant portion of an electron) that cannotb ea ssigned to any nucleus of the molecule, yet is relativelywell localisedin the molecular space.…”
Section: Introductionmentioning
confidence: 99%